Synthesis of new pyrazolo[3, 4‐d]pyrimidine derivatives and evaluation of their anti‐inflammatory and anticancer activities. (6th February 2017) - Abd El Razik, Heba A.; Mroueh, Mohamad; Faour, Wissam H.; Shebaby, Wassim N.; Daher, Costantine F.; Ashour, Hayam M. A.; Ragab, Hanan M.
Abstract : This study reports the synthesis of two series of new purine bioisosteres comprising a pyrazolo[3, 4‐d]pyrimidine scaffold linked to piperazine moiety through different amide linkages. The newly synthesized compounds were evaluated for anticancer activity against four cell lines (MDA‐MB‐231, MCF‐7, SF‐268, B16F‐10) and cyclooxygenase (COX‐2) protein expression inhibition in lipopolysaccharide (LPS)‐activated rat monocytes. The results revealed that most of the synthesized compounds showed moderate‐to‐high cytotoxic activity against at least one cell line, with compound10b being the most active against all used cell lines ( IC 50 values 5.5–11 μg/ml) comparable to cisplatin. In addition, six of these compounds (7b, 10a–d, and12c ) demonstrated inhibition of LPS‐induced COX‐2 protein expression at low concentration (25 μg/ml) as compared to the control non‐stimulated cells and showed a COX‐2 selectivity index range comparable to diclofenac sodium. The overall results indicate that many of these pyrazolopyrimidine derivatives possess in vitro anti‐inflammatory and anticancer activities at varying doses, and the most active compounds will be subjected to in vivo pharmacological evaluation. Abstract : Compounds showing dual anticancer/anti‐inflammatory activity are of increasing interest for the treatment of cancer due to the implication of inflammatory mechanisms in most malignancies. This spurred the synthesis of compounds containing a purine character (a scaffold for anticancer drugs) together with a pyrazole moiety (a scaffold for anti‐inflammatory agents). Among these compounds, 10b was the most active against all used cell lines.